Succession of King Hamengku Buwono X Ngayogykarta - RIZAL, A.N.S. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT King is God’s representative who does not submit to the king of the same as opposing God’s will. In a king, the soul is saved on integrity and truth emit because a king can absorb supernatural forces in himself. The Javanese enthroned king was basically one who could not be entered by people from outside the Keraton. The Javanese concept said political power is not something that can be contested. Political power is something that is passed down and is come directly from the revelation of the Almighty. RESUMEN El rey es el representante de Dios que no se somete al rey de la misma manera que oponerse a la voluntad de Dios. En un rey el alma se salva en integridad y la verdad se emite, porque un rey puede absorber fuerzas sobrenaturales en sí mismo. El rey entronizado de Java era básicamente a quien no podía entrar gente de fuera del Keraton. El concepto javanés dice que el poder político no es algo que pueda ser disputado. El poder político es algo que se transmite y proviene directamente de la revelación del Todopoderoso.